PERTUMBUHAN BAKTERI SALURAN PENCERNAAN PADA MEDIA FERMENTASI REBUNG BAMBU TABAH (Gigantochloa nigrociliata BUZE-KURZ) - Nadiarta, Putu Agus; Antara, Nyoman Semadi; Putra, G.P. Ganda (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 2 (2017): April, 2017)
Shoots of tabah bamboo ( Gigantochloa nigrociliata Buse-Kurz) are known containing oligosaccharides as a prebiotic potential and ability to produce short chain fatty acid in fermention by Lactobacillus casei subsp. rhamnosus . In recent study the fecal bacteria was experimented in fermentation of medium supplemented by bamboo shoot powder (TrYP). The aim of this study was to determine the growth of gastrointestinal bacteria (GI bacteria) during process of fermentation. Fermentation was carried out at 37?C in medium of TrYP and GYP as a control medium. The observation was done from initial of fermentation (0 hour) up to 24 hours in interval of 6 hours. The result were GI bacteria (lactic acid bacteria and faecal coliform) growth until 12 hours fermentation in medium TrYP. The lactic acid bacteria was (11,4 ± 1,34) x 10 9 CFU/ml and the faecal coliform was (1,25 ± 1,13) x 10 9 CFU/ml.   [Keywords]: Gigantochloa nigrociliata , bamboo shoot flour, fermentation, gastrointestinal bacteria.
Keywords: 137